Implementasi Kurikulum Tarbiyatul Muhafadzil Qur’an Untuk Meningkatkan Kemampuan Bahasa Arab, Pemahaman Al Qur’an dan Karakter - Harjo, Budi; Nisa, Qoirul (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This research was conducted with the aim of knowing the implementation of the Tarbiyatul Muhafadzatil Qur'an curriculum at the Rooihatul Jannah Islamic Boarding School, Brumbung, Dukuh, Sukoharjo, Central Java. The Tarbiyatul Muhafadzatil Qur'an curriculum was developed independently, which integrates the teachings of monotheism with the application of the Qur'an in every learning, extracurricular activities, and daily activities. The principle of implementing the Tarbiyatul Muhafadzatil Qur'an curriculum is the deepening, understanding, and mastery of Arabic as a means of understanding the Qur'an. This community service activity was carried out using a group-based Participatory Action Research (PAR) approach, through three stages, which include initial mapping, implementation, evaluation, and reporting. The results of the implementation of the Tarbiyatul Muhafadzatil Qur'an curriculum show several findings, the first of which is that the Tarbiyatul Muhafadzatil Qur'an curriculum integrates religious education and general education, so that students do not only focus on spiritual aspects but also academic ones. Second, the Tarbiyatul Muhafadzatil Qur'an curriculum can improve Arabic language learning outcomes.